Effects of tidal and river discharge forcings on tidal propagation along the Guadiana Estuary - Calero Quesada, Maria Concepcion (2020)
A numerical model is implemented to explore the effect of the river discharge on tidal propagation along the Guadiana Estuary, a rock-bound estuary located in Southwest Iberia. The MOHID numerical model, in 2D barotropic mode, has been forced by tides at the ocean side and by freshwater at the upstream boundary of the domain. The model was validated using water level and velocity observations at several locations along the estuary. Different scenarios with variable tidal forcings and freshwater discharges were analysed, considering the semi- diurnal constituents and M4 overtide, in order to assess the influence of each external agent on the along-channel hydrodynamics. The model reproduces the expected general tidal properties along the channel in terms of amplitude (of both elevation and current), asymmetry and phase between horizontal and vertical tides. Three zones along the estuary have been defined based on the overtide patterns. Tidal propagation in Zone I, at the lower estuary, vary essentially with the tidal amplitude at the mouth while changes due to river discharge are minor. Along Zone II (middle estuary), the tidal forcing still predominates, for low discharge values only. Along Zone III (upper estuary), the tidal propagation is primarily controlled by the river discharge. Although the discharge threshold vary with the location and parameter considered, it is estimated that a discharge as little as 100 m3/s has a strong effect on the tidal properties along the system as a whole. It is therefore concluded that tidal properties in rock-bound estuaries may be importantly modified by relatively weak river discharge events.